Study on Moisture and Durable Properties of Cotton/Hemp Blends Knitted Fabric - Ramsanthosh, K.; Punitha, V. (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
The production of hemp is generally cheaper than cotton. The process of blending the hemp with other conventional natural fibres helps to achieve the textile cloth softer and more durable. The factors influencing moisture management properties of plain knitted fabrics are fibre type, yarn geometry and fabric porosity levels. The study conducted on cotton/hemp blended fabric to analyze the moisture management level of the cloth and to verify the role of fibre type in enhancing the moisture management of fabric.